EXPLORING THE THERAPEUTIC POTENTIAL OF THE MEDICINAL MUSHROOM GANODERMA LUCIDUM (REISHI) - A LITERATURE REVIEW - Barbara Ponitka,; Marta Danuta Cendrowska,; Justyna Berent,; Łukasz Brzost,; Karolina Stępień,; Beata Choromańska,; Paulina Rzepa,; Julia Procyk,; Aleksandra Klukowska,; Julia Maszewska,; Wiktoria Szumlińska,; Szymon Milnerowicz, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Ganoderma lucidum, also known as Reishi, is a medicinal mushroom that has been used for centuries in traditional Asian medicine for its diverse health-promoting properties. Rich in bioactive compounds such as polysaccharides and triterpenoids, G.lucidum exerts various effects such as modulating oxidative stress, inflammation and immune response.Materials and methods: A systematic search of PubMed and Google Scholar was conducted,  using key words and phrases such as “Ganoderma lucidum”, “Reishi”, “properties”, “anticancer”, and  “metabolic health”. A total of 22 high-quality, recent studies relevant to this review were selected for inclusion.Results: This review summarizes evidence on the mushroom's hepatoprotective, neuroprotective, antitumor, cardioprotective, and metabolic effects. Findings from both in vitro and in vivo studies point to its promising role in battling hepatopathies, neurodegenerative disorders, various types of cancer, and metabolic disorders such as dyslipidemia and hypoglycemia.Conclusion: While favorable data from preclinical studies exists, there remains limited data from clinical trials. This review highlights the need for large-scale well-controlled clinical trials to be conducted in order to establish G. lucidum's efficacy, safety, dosing standards, and potential drug interactions.